Pengaruh Penyelesaian Sengketa Tanah Waris melalui Mediasi terhadap Hak Penguasaan Atas Tanah di Desa Nifikiu Kecamatan Amanuban Timur Kabupaten Timor Tengah Selatan - Mary Grace Megumi Maran (Jurnal Hukum Lex Generalis, 2025)
This research examines the influence of customary mediation in resolving inherited land disputes in Nifikiu Village, Amanuban Timor Sub-district, TTS District. The case study shows that customary law-based mediation, such as the Natoni ritual, is an effective alternative to formal litigation. Customary mediation promotes peace, strengthens land tenure rights and maintains social harmony. However, the absence of one of the parties hinders the settlement process. The results show the importance of collaboration between customary law and state law to create fair and sustainable agrarian legal certainty.